PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN TRANSFORMASINAL DAN STRES KERJA TERHADAP KEPUASAN KERJA TENAGA KESEHATAN BRSU TABANAN - Sari, Kadek Dewi Puspita; Sudharma, I Nyoman (E-Jurnal Manajemen, 2017)
Job satisfaction is an assessment of the feelings of individuals, whether or not satisfied with their work in an organization. The importance of job satisfaction encourages many studies that explore the antecedent factors. The purpose of this study was to examine the effect of compensation, transformational leadership style and job stress on job satisfaction. The research was conducted at Badan Tabakit Umum (BRSU) Tabanan. The number of samples taken 87 employees, with the method of Proportional Stratified Random Sampling. Data collection is done through observation, interview and questionnaire. The analysis technique used is multiple linear regression. Based on the results of the analysis found that compensation and transformational leadership style have a positive and significant effect on job satisfaction and work stress have a negative and significant effect on job satisfaction. This research provides information that in order to increase job satisfaction on employees, the management needs to increase financial and non financial compensation to employees, place employees according to their expertise, and provide opportunities for employees in issuing opinions.